Housing and Support Narratives of People Experiencing Mental Health Issues: Making My Place, My Home - Fossey, Ellie; Harvey, Carol; McDermott, Fiona (Frontiers in Psychiatry, 2020)
Background: Choice, control, privacy, and security are widely reported housing preferences of mental health consumers, are associated with improved well-being and greater housing satisfaction, and are important for recovery. This paper describes housing and neighborhood experiences from a larger qualitative study that sought to learn with people experiencing mental health issues about their everyday lives in an Australian urban community. Methods: A participatory approach to health research informed this study. A participatory reference group, including four people with consumer perspective knowledge and experience of mental health issues and four mental health practitioners with service provider and researcher perspectives, worked together to design and implement this study over a 4-year period. Thirty-nine participants were recruited, including 18 women and 21 men living in metropolitan Melbourne and receiving community mental health care for ongoing mental health issues related mainly to either psychotic or affective disorders. Participants each took part in one to three interviews or a focus group. The data were transcribed and analyzed using narrative and thematic analytic strategies, underpinned by reflective discussions with the participatory reference group. Findings: Participants’ experiences of their housing and neighborhoods emphasized qualities that either contributed to or challenged their sense of being “at home.” Identifying with a place as home was transformative, especially when supported by friendly neighborhood interactions, safety, and accessibility of local amenities. Unsatisfactory housing situations and limited income worked against participants’ efforts to regain a sense of well-being and improve their situations. When being home was challenging, strategies used to counteract this included getting a pet and getting out as a means of resisting isolation at home. Differing views and ways of using the available support workers were described, suggesting tensions between seeking to be self-sufficient and valuing support. Conclusions: Social housing locations and housing-related support should explicitly attend to safety and security concerns. Collaborative care planning and outreach support should attend to supports for navigating issues with neighbors, housing, harnessing natural supports, and opportunities for being in others’ company, as well as recognizing the importance of pets in people’s lives. Understanding the strategies that mental health consumers find helpful in creating a sense of being at home, and the role of “place” in recovery merit further consideration in research and practice.